2005
DOI: 10.3354/meps293001
|View full text |Cite
|
Sign up to set email alerts
|

Vertical, lateral and temporal structure in larval distributions at hydrothermal vents

Abstract: We examined larval abundance patterns near deep-sea hydrothermal vents along the East Pacific Rise to investigate how physical transport processes and larval behavior may interact to influence larval dispersal from, and supply to, vent populations. We characterized vertical and lateral distributions and temporal variation of larvae of vent species using high-volume pumps that recovered larvae in good condition (some still alive) and in high numbers (up to 450 individuals sample -1 ).Moorings supported pumps at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 65 publications
3
81
0
Order By: Relevance
“…To consider temporal fluctuations in current patterns, we modeled releases and dispersal between 1998 and 2007 assuming a typical PLD of 6 months [54] and a maximum PLD of 1 year [16]. Initial particle positions were determined with a power function that considered entrainment of larvae in rising hydrothermal plumes up to 400 mab [17] (Supplemental Experimental Procedures). After release, larvae were allowed to drift passively at any depth with the ocean currents, and no assumptions about mortality were made at any time of the simulations.…”
Section: Larval Dispersal Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…To consider temporal fluctuations in current patterns, we modeled releases and dispersal between 1998 and 2007 assuming a typical PLD of 6 months [54] and a maximum PLD of 1 year [16]. Initial particle positions were determined with a power function that considered entrainment of larvae in rising hydrothermal plumes up to 400 mab [17] (Supplemental Experimental Procedures). After release, larvae were allowed to drift passively at any depth with the ocean currents, and no assumptions about mortality were made at any time of the simulations.…”
Section: Larval Dispersal Modelingmentioning
confidence: 99%
“…Arellano and Young [16] concluded that larvae of the cold-seep mussel B. childressi are able to delay the timing of metamorphosis and extend their PLD to a maximum length of 13 months. Because Bathymodiolus veligers can be transported away from the seafloor by passive entrainment in hydrothermal plumes [17] and migrate vertically during their ontogenetic development [18], larvae may be dispersed over large distances in upper ocean currents. How the potential for long-distance dispersal actually shapes population structure and connectivity in these deep-sea organisms is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of free-living symbiotic bacteria at multiple spatial scales within a vent site suggests a potentially large environmental pool of symbionts. During host larval development and the colonization of new vents (17,20,21), an abundant free-living bacterial population would facilitate the initiation of the symbiosis. The environmental transmission of symbionts seems to be a risky strategy for obligate tube worm symbioses, as the survival of the mouthless and gutless adult host requires that developing larvae or juveniles successfully acquire their symbionts from a potentially unstable free-living source population.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Thus, Lepetodrilus spp. and 9 peltospirids are well suited for this assay, rather than sequencing, due to high abundance 10 in the benthos (Van Dover 2003;Dreyer et al 2005) and as larvae in the plankton 11 (Mullineaux et al 2005), and the ability for morphological assignment to a defined 12 species group (genus or family, respectively). 13…”
Section: Identification Of a Defined Group Of Species -Rflp Design 22mentioning
confidence: 99%
“…Micheli et al 2002;Mullineaux et al 2003;4 Govenar et al 2004;Mills et al 2007). High abundances of gastropod larvae in the 5 plankton (Metaxas 2004;Mullineaux et al 2005), multiple modes of development (Lutz 6 et al 1984;Lutz et al 1986), and relative ease of larval identification (Mullineaux et al 7 1996) allow researchers to address questions such as: how do larval development and 8 behavior, and hydrodynamics combine to disperse and/or retain individuals (Lutz et al 9 1980;Marsh et al 2001;Adams and Mullineaux 2008); and what is the impact of 10 dispersal and recruitment on community structure and dynamics? 11 Difficulty in identifying larval stages to the species level can limit studies of 12 larval dispersal (Metaxas 2004;Mullineaux et al 2005).…”
Section: Introduction 20mentioning
confidence: 99%